Emphasizing the properties of soils occurring in different land used of tropical rainforest inSarawak, Malaysia - Jamaluddin, Aiza Shaliha; Abdu, Arifin; Abdul Hamid, Hazandy; Senin, Abdul Latib; Nik Ab. Majid, Nik Muhamad; Jusop, Shamshuddin (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Although, soil properties of tropical rainforest in Southeast Asia have been characterized by several researchers, limited information exists on soil characteristics due to conversion of natural forest into various land use types such as oil palm plantation, rubber plantation, forest plantation and secondary forest. A study was conducted to characterize the soil properties under various land use types of secondary forest (SF), rehabilitation forest (RF), oil palm (OP) and rubber plantation (RP) at Universiti Putra Malaysia, Bintulu, Sarawak, Malaysia. Soil profiles were dug up to 100 cm depth and 50 cm width and were followed by soil sampling according to soil horizon. Soil morphology was determined in the field while soil physico-chemical properties were determined in the laboratory using standard soil analysis. The soils at RF, SF, OP and RP were derived from sandstone intercalated with shale which gives silty loam and sandy clay loam texture. The soils are acidic to weakly acidic with pH increases with depth. The Cation Exchange Capacity (CEC) and Total Carbon (TC) of soils tend to decrease with depth and it seems to be higher under OP and RP as compared to RF and SF. The soils are acidic, highly weathered and considered poor in soil nutrient content.